Heightened BTK-dependent cell proliferation in unmutated chronic lymphocytic leukemia confers increased sensitivity to ibrutinib - Guo, Ailin (Oncotarget, 2015)
In chronic lymphocytic leukemia (CLL), patients with unmutated immunoglobulin heavy chain variable region gene (UM-CLL) have worse outcomes than mutated CLL (M-CLL) following chemotherapy or chemoimmunotherapy. However, in the era of BCR-targeted therapies, the adverse prognostic impact of unmutated IGHV seems to be diminishing, and there are clinical datasets showing unexpected improved responses in UM-CLL. We investigated the biological differences of BTK activity between these subgroups and further compared the impact of ibrutinib on molecular and cellular behaviors. Immunoblotting analysis revealed that phosphorylated active BTK is significantly higher in UM-CLL. Moreover, UM-CLL, compared to M-CLL, displayed a much higher proliferative capacity that was correlated with higher phospho-BTK and greater sensitivity to ibrutinib. In addition, BTK depletion with siRNA led to a more prominent reduction in the proliferation of UM-CLL, suggesting that elevated BTK activity is responsible for increased cell proliferation. Further, cell signaling activity by multiple measurements was consistently higher in UM-CLL accompanied by a higher sensitivity to ibrutinib. These studies link UM-CLL to elevated BCR signaling, heightened BTK-dependent cell proliferation and increased sensitivity to ibrutinib. The prognostic significance of IGHV mutation should be reevaluated in the era of new therapies targeting BCR signaling.